Examining e-Learners’ Preferences and Readiness Satisfaction: A Holistic Modelling Approach - Hale Ilgaz; Yasemin Gülbahar (Open Praxis, 2019)
Over the past several years, online learning has become an extremely popular research topic. Nevertheless, there continues to be a need for a holistic approach when examining online learning. To examine issues related to online learning as well as the effects caused to online learners; researchers in this study developed and tested a model that employed a holistic approach. The aim of this study was to investigate the effect of participants’ learning preferences and readiness to participate in online learning had on their overall satisfaction. The researchers utilized structural equation modelling to determine the relationships that occurred between variables. It was revealed in the results that e-Learners preferences and readiness, which constituted the primary components of this research model, did predict their level of satisfaction with e-learning.